The impact of Basel III on trade finance: The potential unintended consequences of the leverage ratio - Marc Auboin; Isabella Blengini (World Trade Organization (WTO), 2014)
Trade finance, particularly in the form of short-term, self-liquidating letters of credit and the like, has received relatively favourable treatment regarding capital adequacy and liquidity under Basel III, the new international prudential framework. However, concerns have been expressed over the potential "unintended consequences" of applying the newly created leverage ratio to these instruments, notably for developing countries' trade. This paper offers a relatively simple model approach showing the conditions under which the initially proposed 100% leverage tax on non-leveraged activities such as letters of credit would reduce their natural attractiveness relative to higher-risk, less collateralized assets, which may stand in the balance sheet of banks. Under these conditions, the model shows that leverage ratio may nullify in part the effect of the low capital ratio that is commensurate to the low risk of such instruments. The decision by the Basel committee on 12 January 2014 to reduce the leverage ratio seems to be justified by the analytical framework developed in this paper.
Keywords: E44; F13; F34; F36; O19; G21; G32; 330; trade financing; cooperation with international financial institutions; prudential supervision and trade